Developing a Global Cancer Stigma Index. (12th September 2014) - Edelen, Maria Orlando; Chandra, Anita; Stucky, Brian; Schear, Rebekkah; Neal, Claire; Rechis, Ruth
Despite increasing recognition about the stigma associated with cancer screening, diagnosis, and treatment-seeking behaviors, there has been relatively little attention paid to how to assess and intervene to reduce that stigma. An index to measure cancer stigma could empower health program developers and policymakers by identifying the key areas in which a population could benefit from education to change perceptions and address misinformation. The index also could be used to rank countries and communities based on their level of cancer stigma to assess where interventions are needed. We used structured literature review and expert review to generate a cancer stigma item pool. The item pool was subject to cognitive interviews for cultural appropriateness and comprehension; and data from initial pilot testing were used to reduce the pool of items for translation and field testing. The field test was conducted using a web-based survey in four samples representing two regions and three languages—English and Arabic speakers in Jordan and Egypt, and English and Mandarin Chinese speakers in China. Factor analyses and item response theory were applied to finalize the index. The analyses resulted in a 12-item cancer stigma index (CSI) that was reliable across all four samples. The CSI scores were highly correlated with a general illness stigma scale, and operated as expected noting higher cancer stigma among men and those with lower income. The CSI can be used to inform initial cancer education efforts, identifying overall stigma levels in a country or community and particular issue areas requiring intervention.